Effects of Using Instructional Model Using Process of Group Teaching through Reflection to Enhance Academic Achievement and Critical Thinking Skills and Problem Solving for Nursing Students of The Royal Thai Army Nursing College - สว่างจิตร ศิริพร; กังหลี กุสุมา; กลิ่นเชตุ นันทิกานต์ (Journal of The Royal Thai Army Nurses, 2019)
This quasi-experimental research aimed to compare the academic achievement of nursing students using pre-and post-test after applying the instructional module by using the process of group teaching through reflection. Additionally, this research aimed to compare the critical thinking and problem solving skills of nursing students by using the instructional model.,the purposive sampling method was used to recruit the sample, including 98 students from the 1st year of the Royal Thai Army Nursing College (RTANC). In addition, the academic achievement test and a form for measuring the critical thinking and problem solving skills were used to collect the data. The data, then, were analyzed by using percentage, mean, Standard Deviation (S.D.), and paired sample t-test statistics. This research found that the mean score of the pre-test of the academic achievement was 14.74 (S.D. 2.79), Whereas the mean score of the post-test of the academic achievement was 19.24 (S.D. 2.85). Importantly, the mean difference of the academic achievement between pre-and post-test of the students was statistically significant (P-valve 0.01). For the critical thinking and problem solving skills, The mean score of the pre-and post-test was 25.45 (S.D. 3.76), while the mean score of the post-test was 26.51. (S.D. 2.78). Also, the mean difference between the pre-and post-test of the critical thinking and problem solving skills was statistical significance (P-valve 0.01). It can be seen that using of the instructional model by applying the process of group teaching trough reflection can enhance the academic achievement and the critical thinking and problem solving skills of the RTANC nursing students, which could develop students’ learning skills in the 21st century.